2015
DOI: 10.1186/s12911-015-0188-9
|View full text |Cite
|
Sign up to set email alerts
|

Experience of using mHealth to link village doctors with physicians: lessons from Chakaria, Bangladesh

Abstract: BackgroundBangladesh is facing serious shortage of trained health professionals. In the pluralistic healthcare system of Bangladesh, formal health care providers constitute only 5 % of the total workforce; the rest are informal health care providers. Information Communication Technologies (ICTs) are increasingly seen as a powerful tool for linking the community with formal healthcare providers. Our study assesses an intervention that linked village doctors (a cadre of informal health care providers practising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 29 publications
2
43
0
Order By: Relevance
“…A second approach is use of telemedicine or teleconsultation to link inexperienced providers with mentors to help navigate buprenorphine OMT procedures. These approaches are becoming more widely used in general medicine (Biery, Bond, Smith, LeClair, & Foster, 2015; Eaton et al, 2015; Gillis, 2015; Khan et al, 2015; Marcolino, Pereira Afonso Dos Santos, Santos Neves, & Alkmim, 2015), have been associated with reductions in medical errors or referrals to formal treatments (Campanella et al, 2015), and have particular value for remote or rural areas (Saurman, Lyle, Perkins, & Roberts, 2014) for which research has indicated there is a dearth of available opioid treatment options (Blum et al, 2016; Cunningham et al, 2007; Jones et al, 2015; Knudsen et al, 2005; Knudsen, 2015). The Physician Clinical Support System-Buprenorphine(PCSS-B) is a federally funded program that is already in place to pair newly waivered physicians with an experienced provider usually via telephone or email, but possibly with in-person meetings as well (Egan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A second approach is use of telemedicine or teleconsultation to link inexperienced providers with mentors to help navigate buprenorphine OMT procedures. These approaches are becoming more widely used in general medicine (Biery, Bond, Smith, LeClair, & Foster, 2015; Eaton et al, 2015; Gillis, 2015; Khan et al, 2015; Marcolino, Pereira Afonso Dos Santos, Santos Neves, & Alkmim, 2015), have been associated with reductions in medical errors or referrals to formal treatments (Campanella et al, 2015), and have particular value for remote or rural areas (Saurman, Lyle, Perkins, & Roberts, 2014) for which research has indicated there is a dearth of available opioid treatment options (Blum et al, 2016; Cunningham et al, 2007; Jones et al, 2015; Knudsen et al, 2005; Knudsen, 2015). The Physician Clinical Support System-Buprenorphine(PCSS-B) is a federally funded program that is already in place to pair newly waivered physicians with an experienced provider usually via telephone or email, but possibly with in-person meetings as well (Egan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…mHealth, or mobile health, projects have shown to be increasingly successful in developing countries. Collecting health data (8)(9)(10), increasing access to health knowledge (11)(12)(13)(14), promoting provider quality (15)(16)(17), and increasing medication/appointment adherence (18)(19)(20) are a few ways in which mobile phones have successfully been used in developing countries to support health. In addition, rigorous evaluations have demonstrated mobile phone messages to be successful in supporting preventative healthcare (8,14,18,21,22) such as chronic disease prevention in Seychelles (23).…”
Section: Introductionmentioning
confidence: 99%
“…That is, the BYOD policy should cater for other mobile device uses such as diagnosis [45,[57][58][59][60][61], patient monitoring, follow-up [46,[62][63][64][65][66], data collection [43,46,51,67], and medication adherence [68,69]. Integration of mobile devices into hospital systems, especially patient record management [70], including patient participation in computerized patient record management [71], is also worth policy consideration.…”
Section: Discussionmentioning
confidence: 99%